THYMOPOIESIS INTENSITY IN PATIENTS WITH BRONCHIAL ASTHMA, DEPENDING ON DURATION OF THE DISEASE - E. A. Blinova; V. M. Nepomniashchikh; V. S. Kozhevnikov (Медицинская иммунология)
Abstract. Functional activity of thymus in normal donors and patients with various clinical forms of bronchial asthma was evaluated by means of assessing TREC-positive T-cell numbers. In spite of well-known alterations in parameters of T-cell homeostasis, TREC levels in CD4+and CD8+ lymphocytes from the patients with asthma did not differ significantly from those in donors. There were also no significant differences in TREC-containing cell numbers, dependent on clinical types of bronchial asthma and IgE levels. However, the patients with a recent disease onset (duration of several days to one year) showed increased TREC positivity in CD4+ and CD8+ lymphocytes, as compared with donors and those patients who underwent basal therapy with glucocorticoids, and during long-term disorder (> 1 year). Enhanced thymopoiesis at initial stages of the disease may be associated with thymic stromal lymphopoietin which contributes to development of bronchial asthma, and normally participates in the process of T cell production.